2022
DOI: 10.3390/nu14153135
|View full text |Cite
|
Sign up to set email alerts
|

A Low-Phenylalanine-Containing Whey Protein Hydrolysate Stimulates Osteogenic Activity through the Activation of p38/Runx2 Signaling in Osteoblast Cells

Abstract: A phenylalanine (Phe)-restricted diet is indispensable for individuals suffering from phenylketonuria (PKU). Our previous study reported a low-Phe-containing whey protein hydrolysate (LPH) prepared from a selected whey protein hydrolysate (TA2H). This study aimed to investigate the osteogenic activity of LPH and TA2H in MC3T3-E1 preosteoblast cells and explore the underlying mechanism. Results showed that the treatment of TA2H and LPH (at the final concentrations of 100–1000 μg/mL) had a stimulatory effect on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Our previous studies reported that the WPH could regulate the homeostasis of bone metabolism in vitro and in vivo [ 25 , 27 ]. To further identify the specific peptides with high osteogenic and antioxidative potentials, WPH was separated into 16 fractions by RP-HPLC ( Figure 1 a); among which F9 possessed both significantly higher osteogenic capacity and DPPH scavenging activity than other fractions ( Figure 1 b).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous studies reported that the WPH could regulate the homeostasis of bone metabolism in vitro and in vivo [ 25 , 27 ]. To further identify the specific peptides with high osteogenic and antioxidative potentials, WPH was separated into 16 fractions by RP-HPLC ( Figure 1 a); among which F9 possessed both significantly higher osteogenic capacity and DPPH scavenging activity than other fractions ( Figure 1 b).…”
Section: Resultsmentioning
confidence: 99%
“…Whey-derived antioxidant peptide YVEEL ameliorated osteoporosis in an ovariectomized rat model by suppressing inflammation and enhancing osteogenesis [ 24 ]. We previously reported a whey protein enzymatic hydrolysate (WPH) exerted effects on activating osteogenesis and preventing ovariectomy-induced osteoporosis through regulating the p38/mitogen-activated protein kinase (MAPK)/Runx2 signaling pathway [ 25 , 26 , 27 ]. Although the anti-obesity/adipogenesis function of milk proteins, as well as their derived bioactive peptides, has been reported previously [ 28 , 29 ], the regulation effects of WPH on HFD-induced bone loss through redox modulation have not been sufficiently investigated.…”
Section: Introductionmentioning
confidence: 99%
“…7 Conversely, osteoclastogenesis inhibitory factor (osteoprotegerin, OPG), a soluble protein from osteoblasts, competes with receptor activator of nuclear factor-kappaB ligand (RANKL) to antagonize the RANK-RANKL interaction, thereby inhibiting osteoclastogenesis and preserving the osteogenic environment. 8,9 Therefore, osteogenesis is a key process in the inhibition of bone loss.…”
Section: Introductionmentioning
confidence: 99%
“…In endothelial cells exposed to diabetic conditions, treatment with whey hydrolysate prevented mitochondrial injury and redox imbalance [25]. Increased GSH levels in plasma and erythrocytes have also been reported in rats which were fed a diet supplemented with 10% whey proteins [26,27], but the evidence for its protective effects on vascular functions in humans remains unsubstantiated [28] Regarding tissue engineering applications, several reports have indicated that WPI dissolved in cell culture medium stimulates the osteogenic differentiation of bone-forming cells [12,[29][30][31]. However, in the majority of the previous studies, WPI has been used only as a supplement for cell culture medium, in the form of lysate or dissolved powder.…”
Section: Introductionmentioning
confidence: 99%